Development of a new recombinant starter culture bacterium for milk coagulation - Raftari, Mohammad (2013)
Milk clotting enzyme is the key factor for the production of different types of cheese. Hence, calf rennet (chymosin) is traditionally used as a milk coagulant in cheese manufacturing. As the increase in cheese manufacturing globally, coincided with a decline in the supply of calf rennet, it became imperative that substitutes for rennet be found. Recently, the use of fungal mucor rennin, in industrial cheese manufacturing, has become prevalent. Lactococcus lactis is a lactic acid bacterium which is generally used as a starter in dairy industries for the production of various types of hard and soft cheeses. Therefore, due to the key role of milk clotting enzyme as well as starter culture bacteria in cheese manufacturing, this study was an attempt to express recombinant mucor rennin (MPR) enzyme by L. lactis to produce milk coagulation enzyme. It is a novel milk clotting procedure using recombinant bacterium capable of milk coagulation. To achieve this, the amplified MPR gene was sub-cloned into pAMJ-LacF expression vector. The food grade pAMJ-LacF expression vector was created by sub-cloning the amplified LacF gene in pAMJ399 vector which lost its erythromycin gene. The recombinant pAMJ-LacF-MPR vector was then electro-transferred into L. lactis NZ3900 and plated onto Elliker-L medium. The plasmid extraction and restriction digestion methods were performed to check the presence of insertion; in addition, the SDS-PAGE and western blotting were carried out to detect the MPR protein expression of recombinant L. lactis carrying MPR gene. The protein assay, milk clotting activity (MCA) and proteolytic activity (PA) of purified recombinant MPR protein were also studied after optimizing the growth rate, and protein expression of recombinant L. lactis carrying MPR gene. Finally, milk coagulation ability of recombinant L. lactis carrying MPR gene was tested. Nucleotide sequencing of DNA insertion from the clone revealed that the MPR activity corresponded to an open reading frame consisting of 1218 bp coding for a 43.45-kDa MPR protein. A clear band on 43.45-kDa size on SDS-PAGE and western blotting confirmed the successful expression of MPR protein by recombinant L. lactis. Optimizing the growth rate of recombinant L. lactis showed the highest cell biomass for the cultures incubated at 33°C. The MPR protein assay results indicated that the highest MPR enzyme, approximately 65.6 μg/ml.h, were obtained for cultures which were incubated at pH 5.5 and 30°C. Statistical analysis of results revealed that there was no significant difference (P<0.05) between MPR protein expression at 30 and 33°C but a significant difference was noted with the expressed MPR protein at 27 and 36°C. Analysis of the mean of the results of milk clotting activity and MCA/PA of purified recombinant MPR protein for the highest purified levels of expressed protein at pH 5.5 and temperatures 30, 33, 27 and 36°C and control showed 870.54, 809.86, 491.85, 358.54 and 651.38 SU/ml for milk clotting activity and 7914, 7362.36, 4471.36, 3259.45 and 5664.17 SU/OD for MCA/PA,respectively. The thermal and pH stability results of purified recombinant MPR protein showed that the recombinant MPR protein is stable at the pH range 3.5–7.5 and thermal stability range 20-50°C. Interestingly, milk coagulation was observed after inoculating milk with recombinant L. lactis carrying MPR gene due to the high expression rate of MPR enzyme by recombinant L. lactis. The mean of the results indicated that the milk coagulated after 220 and 205 min when inoculated milk were incubated at 33°C, under static and agitation conditions, respectively. The curd yield results showed 14.35 g/100ml compared to 13.86 g/100ml solid curd for milk added recombinant L. lactis carrying MPR gene and commercial rennet, respectively. The plasmid stability results also showed that the recombinant pAMJ-LacF-MPR vector has high stability around 88.9% after 200 generations in L. lactis. This study presents novel findings, as the L. lactis was used for the first time as a cell factory for the production of recombinant rennin. In addition, this study introduced a novel milk clotting procedure using recombinant bacterium capable of milk coagulation. The recombinant L. lactis carrying MPR gene, created in this study, has the ability to function as starter culture for acidifying and subsequently coagulating milk by producing mucor rennin as the milk coagulant agent. Thus, these findings would have a significant impact on the cheese industry.